THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND BREAKFAST HABITS WITH LEARNING ACHIEVEMENT IN STUDENTS OF SD NEGERI 28 SUNGAI LANGKA, GEDONG TATAAN DISTRICT, PESAWARAN REGENCY IN 2019 - Eka Yuliani; Karyawanto Karyawanto; Dwi Yulia (Jurnal JKFT, 2025)
The state of nutritional status and grade point average is a description of what elementary school children consume in the long term, which can be in the form of undernutrition or overnutrition. Nutrients such as protein carbohydrates, as well as other nutrients, especially iron, play a role in the body's metabolism in thinking processes or reasoning processes as well as concentration power and are very closely related to learning efficiency. With a good nutritional state is expected to have an impact on good learning achievement. The purpose of this study was to determine the relationship between nutritional status and breakfast habits and learning achievement in grades IV and V SD Negeri 28 Sungai Langka, Gedong Tataan District, Pesawaran Regency. The type of research used in this research is quantitative. The design in this study uses an analytical survey, using a cross sectional approach. The population in this study were students in grades IV and V of SD Negeri 28 Sungai Langka, Gedong Tataan District, Pesawaran Regency, totaling 51 people. The sample technique in this study uses Total Sampling. The results of the study determined that there was a relationship between nutritional status and learning achievement with a p-value of 0.028 and there was a relationship between breakfast habits and learning achievement in students of SD Negeri 02 Sungai Langka, Gedong Tataan District, Pesawaran Regency in 2019 with a p-value of 0.036 and OR: 4.071 . It is expected to provide education to students about the importance of choosing healthy and nutritious food and provide input to parents of students to provide healthy and nutritious food.